A Critique of Yoruba Religio-cultural Belief in Reincarnation in Light of Hikmat al-Muta’āliya (Islamic Transcendent Philosophy) - Olawale, Abdulwasi; Bakhshayesh, Reza (Journal of Ecohumanism, 2025)
Man’s quest to understand life after death leads him to the concept of reincarnation. Reincarnation is the transmigration of human soul into another body. However, the African, especially the Yoruba concept of reincarnation is quite different from the Asian belief in certain aspects, and this is better explained in the three types of reincarnation common amongst them., viz: Ìpadàwáyé (ancestor’s rebirth), Àkúdáàya (reappearance after death) and Àbíkú (born to die). Even though few African philosophers have critiqued African’s reincarnation concept, but there persist unsatisfactory analysis and unanswered questions. This article, using descriptive-analytical method is unprecedented as it critiques Yorùbá’s concept of reincarnation in light of Mulla Sadra’s transcendent philosophy. Sadra’s positions on the nature of Soul, substantial motion of the body and soul, etc., proved the impossibility of reincarnation of any form. Finally, this research also resolves other problems associated with Yorùbá’s concept of reincarnation.